Analysis of Leading Sectors in Increasing Economic Growth in the Province of East Nusa Tenggara in 2014-2018 - Emilia Khristina Kiha; Frederic Winston Nalle; Gustaf Inyong Kobi (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2021)
The aims of the study is to find out the leading sectors in increasing economic growth in the province of east nusa tenggara. This study uses secondary data in the form of PDRB data for the 2014-2018 period obtained through literature books, readings related to the problem under study. Sources of data were obtained from government agencies such as the East Nusa Tenggara Province Central Statistics Agency (BPS), as well as related agencies. The result in this study. 1. Based on the results of the Klassen Typology analysis, the sector which is included in the advanced sector and growing rapidly or the leading sector is the sector Mandatory Government Administration, Defense and Social Security. Meanwhile, sectors that are included in the advanced but depressed sector are the Agriculture, Forestry and Fisheries sector, the Construction sector, the Transportation and Warehousing sector, the Information and Communication sector, the Education Services sector, the Health Services sector and Social Activities and the Other Services sector. Sectors classified as potential or still developing sectors are mining and quarrying sector, processing industry sector, electricity and gas supply sector, wholesale and retail trade: car and motorcycle repair and accommodation and food and drink provision sector. Meanwhile, sectors that are relatively lagging behind are the water supply sector, waste management, waste and recycling, the financial services and insurance sector, the real estate sector and the corporate services sector.